Comparison of two bacterial DNA extraction methods from non-polluted and polluted soils - Mazziotti, Mélanie; Henry, Sonia; Laval-Gilly, Philippe; Bonnefoy, Antoine; Falla, Jaïro (Folia microbiologica, 2018)
DNA extraction from soil samples is a critical step for molecular biology analyses. The present study compared the efficiency of two DNA isolation methods from non-polluted and polluted soils with or without the presence of a plant. Both applied methods used chemical and physical lyses, but method 1 had an additional physical disruption. The main difference between these two methods was the humic acid purification technique as it was carried out during cell lysis for method 1 and after cell lysis for method 2. Samples were assessed on the basis of their yield and DNA purity as well as their bacterial quantity and diversity. Based on our results, method 1 proved to be more effective at removing protein and RNA, whereas method 2 proved to be more effective at removing humic acids. Although no differences were obtained in terms of the DNA yield, both the bacterial quantity and community structure were affected by the method used. Method 1 allowed for the recovery of more information than method 2, and polluted soil was more sensitive to the DNA extraction procedure. We recommend carefully selecting the DNA extraction method, especially when soil is disturbed.
Keywords: DNA, Bacterial; znečištění životního prostředí; polymerázová řetězová reakce; Soil; Humic Substances; chemické techniky analytické; půdní mikrobiologie; látky znečišťující půdu; Soil Microbiology; DNA bakterií; huminové látky; Chemistry Techniques, Analytical; Bacteria; Environmental Pollution; půda; Polymerase Chain Reaction; Soil Pollutants